Metabolomics reveal the mechanism for anti-renal fibrosis effects of an n-butanol extract from Amygdalus mongolica - Gao Chen; Chang Hong; Zhou Hong-Bing; Liu Qing; Bai Ying-Chun; Liu Quan-Li; Bai Wan-Fu; Shi Song-Li (Acta Pharmaceutica)
To reveal the mechanism of anti-renal fibrosis effects of an n-butanol extract from Amygdalus mongolica, renal fibrosis was induced with unilateral ureteral obstruction (UUO) and then treated with an n-butanol extract (BUT) from Amygdalus mongolica (Rosaceae). Sixty male Sprague-Dawley rats were randomly divided into the sham-operated, renal fibrosis (RF) model, benazepril hydrochloride-treated model (1.5 mg kg−1) and BUT-treated (1.75, 1.5 and 1.25 g kg−1) groups and the respective drugs were administered intragastrically for 21 days. Related biochemical indices in rat serum were determined and histopathological morphology observed. Serum metabolomics was assessed with HPLC-Q-TOF-MS. The BUT reduced levels of blood urea nitrogen, serum creatinine and albumin and lowered the content of malondialdehyde and hydroxyproline in tissues. The activity of superoxide dismutase in tissues was increased and an improvement in the severity of RF was observed. Sixteen possible biomarkers were identified by metabolomic analysis and six key metabolic pathways, including the TCA cycle and tyrosine metabolism, were analyzed. After treatment with the extract, 8, 12 and 9 possible biomarkers could be detected in the high-, medium- and low-dose groups, respectively. Key biomarkers of RF, identified using metabolomics, were most affected by the medium dose. A. mongolica BUT extract displays a protective effect on RF in rats and should be investigated as a candidate drug for the treatment of the disease.